2021
DOI: 10.3390/s21092987
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Layer Classification Approach for Intrusion Detection in IoT Networks Based on Deep Learning

Abstract: The security of IoT networks is an important concern to researchers and business owners, which is taken into careful consideration due to its direct impact on the availability of the services offered by IoT devices and the privacy of the users connected with the network. An intrusion detection system ensures the security of the network and detects malicious activities attacking the network. In this study, a deep multi-layer classification approach for intrusion detection is proposed combining two stages of det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 70 publications
1
40
0
Order By: Relevance
“…RLSTMs are highly rated RNN variants as they have the capability to tackle the problem of long-term dependencies of RNN [44]. In addition, they provide long-term memory, and they have the capacity of addressing the problem of vanishing gradients that might occur when training traditional RNNs [45,46]. They can process an entire sequence of data and not just the single data points.…”
Section: Refined Long Short-term Memory (Rlstm)mentioning
confidence: 99%
“…RLSTMs are highly rated RNN variants as they have the capability to tackle the problem of long-term dependencies of RNN [44]. In addition, they provide long-term memory, and they have the capacity of addressing the problem of vanishing gradients that might occur when training traditional RNNs [45,46]. They can process an entire sequence of data and not just the single data points.…”
Section: Refined Long Short-term Memory (Rlstm)mentioning
confidence: 99%
“…With a ratio of 0.9 and a k value of 3 for the k-means++ clustering technique, the results showed that using the SLFN classification technique and using the SVM and synthetic minority oversampling technique (SVM-SMOTE) yielded more accurate results than using other values and classification techniques. Similarly, a deep multi-layer classification strategy was suggested by Quddoura et al [110], which consisted of two phases of detection. The first phase entails detecting the presence of an intrusion and the second phase identifies the kind of intrusion.…”
Section: Malicious Traffic In a Cloud Environmentmentioning
confidence: 99%
“…where the Precision is the percentage of correct predictions for a class relative to all the predictions of the same class [61], and the Recall is the percentage of correct predictions for a class relative to all instances that actually belong to the class [62].…”
Section: Evaluation Measuresmentioning
confidence: 99%